The Effects of Online Collaborative Learning (OCL) on Student Achievement and Engagement - Ana Liza Villano Gaad (IAFOR Journal of Education, 2022)
This study determined the effects of Online Collaborative Learning (OCL) on student achievement and engagement in physical science. A one-group pretest/posttest pre-experimental research design was employed. The participants were Grade 11 students (n=30) in a public stand-alone senior high school in Congressional District 1, Quezon City, Philippines, who were selected using purposive sampling. This study utilized five research instruments: (1) OCL-based lesson plans, (2) Learning Activity Sheets (LAS), (3) Physical Science Achievement Test (PSAT), (4) CIP Engagement Questionnaire, and (5) Student Learning Experience Survey. The collected data were analyzed and interpreted quantitatively and qualitatively. Quantitative data were obtained from the validated 40-item achievement test and the adopted engagement questionnaire, while responses to the Student Learning Experience Survey provided qualitative data. Paired t-test was employed to determine the significant difference in achievement and engagement before and after the OCL’s implementation. The results showed a significant difference between the pretest and posttest mean scores of the students in the achievement and engagement in physical science. Likewise, there was a statistically significant difference between the pretest and posttest mean scores for all engagement factors: cooperation, interest, and participation. The result of the survey revealed that students’ exposure to the OCL strategy was effective in facilitating significant improvements in their achievement and engagement in physical science. Overall, the findings signified that Online Collaborative Learning (OCL) as a teaching-learning strategy enhanced students’ achievement and engagement in physical science.